2018
DOI: 10.1073/pnas.1811887116
|View full text |Cite
|
Sign up to set email alerts
|

Structured environments fundamentally alter dynamics and stability of ecological communities

Abstract: The dynamics and stability of ecological communities are intimately linked with the specific interactions—like cooperation or predation—between constituent species. In microbial communities, like those found in soils or the mammalian gut, physical anisotropies produced by fluid flow and chemical gradients impact community structure and ecological dynamics, even in structurally isotropic environments. Although natural communities existing in physically unstructured environments are rare, the role of environment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…This is in accordance with previous theoretical studies on effects of dispersal (Engen et al 2002, Walter et al 2017. Underlying spatial structure, caused by, for example, heterogeneity in resource availability, can have an additional impact on how organisms distribute themselves in space (Cohen andLevin 1991, Vallespir Lowery andUrsell 2019), which we have not considered in the spatially homogenous model presented here. Studies from several taxa have shown that environmental fluctuations can have a synchronizing effect on population dynamics of different species (Myers 1998, Post and Forchhammer 2002, Hansen et al 2013, Lahoz-Monfort et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous theoretical studies on effects of dispersal (Engen et al 2002, Walter et al 2017. Underlying spatial structure, caused by, for example, heterogeneity in resource availability, can have an additional impact on how organisms distribute themselves in space (Cohen andLevin 1991, Vallespir Lowery andUrsell 2019), which we have not considered in the spatially homogenous model presented here. Studies from several taxa have shown that environmental fluctuations can have a synchronizing effect on population dynamics of different species (Myers 1998, Post and Forchhammer 2002, Hansen et al 2013, Lahoz-Monfort et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In homogeneous (and disturbed) environments, species which monopolize resources fastest will probably dominate, resulting in a chimeric outcome composed of the most competitive species from input communities [25,26]. By contrast, more structured environments can promote coexistence between species by limiting interaction intensity as niche boundaries are greater [36,37]. In these environments, coalescence outcomes are expected to be more modular as mixing between communities is limited and interactions become more localized.…”
Section: Resident Advantage and Abiotic Adaptationmentioning
confidence: 99%
“…Here, ̂ is the scaled distance parameter, is the unscaled distance variable, is the diffusion constant of the resource, and µ is the organism's growth or uptake rate. A similar natural length scale was recently observed in a Lotka-Volterra model (Vallespir Lowery & Ursell, 2018), but its relevance to adaptation has not been explored. Does increasing ̂ increase the amount of structured interactions?…”
Section: Figurementioning
confidence: 66%